Implikasi Media Sosial terhadap Lima Nilai Pendidikan Karakter pada Peserta Didik Kelas V di MIN 1 Kolaka Utara: Penelitian - Ummu Kalsum Amaliyah; Supriadi; Mas’adi; Muslim AR (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Social media and the five main values ​​of character education are important in the advancement of education. This study aims to examine the implications of social media use on fifth-grade students at MIN 1 Kolaka Utara, which has a positive impact on the five main values ​​of character education, namely religious, nationalist, independent, integrity, and mutual cooperation. This study uses a quantitative research type with a linear regression research design. The research data collection technique used a questionnaire aimed at students. The results of this study indicate a significant relationship between social media use and the five main values ​​of character education with a significance value (Sig.) of 0.018, smaller than the general threshold of 0.05. Overall, perceptions of social media are very positive. The average score is above 80% of the maximum total, which means that respondents view social media as having a role that helps students in learning and obtaining positive information to support learning. Meanwhile, character education is above 4.0, which indicates that students demonstrate religious, nationalist, independent, integrity, and mutual cooperation behavior.